Physicochemical properties of milk protein ingredients and their acid gelation behaviour in different ionic environments. (October 2018) - Liu, Guanchen; Jæger, Tanja C.; Nielsen, Søren B.; Ray, Colin A.; Ipsen, Richard
Abstract: Dispersions of whey protein isolate (WPI), microparticulated whey protein (MWP), nanoparticulated whey protein (NWP) and micellar casein isolate (MCI) were characterised in terms of protein denaturation and particle size. WPI exhibited high native whey protein content, while MWP and NWP showed low native whey protein content. The acid gelation behaviour of milk protein ingredients and mixtures thereof (5% protein) in different ionic environments (deionised water, whey permeate and dialysed against skimmed milk) was also investigated. The gelation curves of NWP showed no significant difference for in the three different ionic environments, and high gel strength after acidification was observed. WPI, MWP and MCI dispersed in deionised water gelled faster than in the other two ionic environments. MCI in whey permeate showed slower gelation and lower G' than their dialysed samples.